An Update on the Pathogenesis of COVID-19 and the Reportedly Rare Thrombotic Events Following Vaccination - Kantarcioglu, Bulent; Iqbal, Omer; Walenga, Jeanine M.; Lewis, Bruce; Lewis, Joseph; Carter, Charles A.; Singh, Meharvan; Lievano, Fabio; Tafur, Alfonso; Ramacciotti, Eduardo; Gerotziafas, Grigoris T.; Jeske, Walter; et al. (Clinical and applied thrombosis/hemostasis, 2021)
Today the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has become a global health problem. After more than a year with the pandemic, although our knowledge has progressed on COVID-19, there are still many unknowns in virological, pathophysiological and immunological aspects. It is obvious that the most efficient solution to end this pandemic are safe and efficient vaccines. This manuscript summarizes the pathophysiological and thrombotic features of COVID-19 and the safety and efficacy of currently approved COVID-19 vaccines with an aim to clarify the recent concerns of thromboembolic events after COVID-19 vaccination. The influx of newer information is rapid, requiring periodic updates and objective assessment of the data on the pathogenesis of COVID-19 variants and the safety and efficacy of currently available vaccines.